A cross sectional study of heat stress exposure, heat -realted symptoms, and kidney health among kitchen workers in Kampar, Perak Malaysia - Koh, Abigail Shu Hong (2024)

(untitled)
Background: Kitchen workers are one of the heat-exposed occupations that are exposed to heat stress due to their work nature which requires them to work with radiant heat sources, coupled with poor ventilation and high humidity in the kitchen areas. These working conditions increase their risk of experiencing heat-related illnesses and heat-related symptoms. Heat stress coupled with dehydration also contributed to the risk of kidney-related complications, such as kidney stones and urinary tract infections. Aim and objectives: This study aims to study heat stress exposure, heat-related symptoms, and kidney health among kitchen workers in Kampar, Perak. Methodology: This cross-sectional study recruited 62 kitchen workers from local restaurants or hawker stalls in Kampar. Environmental monitoring, such as wet bulb globe temperature (WBGT), temperature, humidity, and thermal work limit was conducted in 14 kitchen areas of study respondents for three days using the Kestral 5400 WBGT Heat Stress Tracker. A self-administered structured questionnaire was also distributed to the participants to collect demographic information, living habits, working-related information, heat-related symptoms, and kidney-related symptoms of the participants. Urine samples of the participants (n=53) were collected pre-shift and post-shift to study their hydration status and kidney health using urinalysis dipstick tests. The collected data were keyed in and analysed using IBM SPSS Statistics version 21. Wilcoxon Signed Rank test was conducted to compare urine test parameters in the urine samples of pre-shift and post-shift, and the Mann-Whitney U test was conducted to study the relationships between heat-related illnesses and kidney health, and the relationships between demographic factors, living habits, and working factors with heat-related symptoms. Results: In this study, The mean ± standard deviation (SD) for WBGT, temperature, relative humidity, and thermal work limit measured across 14 kitchen areas were 27.2 ± 1.0 °C, 29.9 ± 1.6 °C, 75.2 ± 6.2 %, and 157.5 ± 20.4. The mean WBGT of 27.2°C did not exceed the Threshold Limit Value established by the American Conference of Governmental Industrial Hygienists (ACGIH), i.e., 28°C, but exceeded the action limit of 25°C. In this study, 38.7% of the participants were identified as having heat-related illnesses with the most frequently reported heat related symptoms being heavy sweating (45.1%), thirst (25.8%), and weakness/fatigue (24.2%). From the urinalysis dipstick test, it was found that there were no significant differences in the 10 parameters of the urine test between pre-shift and post-shift urine samples. There was also no significant association determined between kidney health and heat-related illnesses among the study respondents. Frequency of drinking caffeinated drinks was negatively related to vomiting symptoms (U=0.500, p=0.049), while the perception of respondents on feeling hard about their work was positively related to heavy sweating (U=339.5, p=0.039), weakness or fatigue (U=340.5, p=0.033), dizziness (U=122.0, p=0.031) and irritability (U=285.0, p=0.039). Conclusion: Kitchen workers in Kampar were identified as having a medium risk of heat stress and are advised to apply general controls recommended by ACGIH guidelines. More studies are required to further investigate the relationship between heat stress exposure with kidney health as well as risk factors that contribute to heat related symptom